FeIII48‐Containing 96‐Tungsto‐16‐Phosphate: Synthesis, Structure, Magnetism and Electrochemistry. Issue 68 (3rd November 2020) - Goura, Joydeb; Bassil, Bassem S.; Bindra, Jasleen K.; Rutkowska, Iwona A.; Kulesza, Pawel J.; Dalal, Naresh S.; Kortz, Ulrich
Abstract: The 48‐Fe III ‐containing 96‐tungsto‐16‐phosphate, [Fe III 48 (OH)76 (H2 O)16 (HP2 W12 O48 )8 ] 36− (Fe48 ), has been synthesized and structurally characterized. This polyanion comprises eight equivalent Fe III 6 P2 W12 units that are linked in an end‐on fashion forming a macrocyclic assembly that contains more iron centers than any other polyoxometalate (POM) known to date. The novel Fe48 was synthesized by a simple one‐pot reaction of an Fe22 coordination complex with the hexalacunary P2 W12 POM precursor in water. The title polyanion was characterized by single‐crystal XRD, FTIR, TGA, magnetic and electrochemical studies. Abstract : A very large, discrete 96‐tungsto‐16‐phosphate containing 48 Fe III centers, [Fe III 48 (OH)76 (H2 O)16 (HP2 W12 O48 )8 ] 36− (Fe48 ), has been synthesized and structurally characterized. Polyanion Fe48 comprises eight equivalent Fe6 P2 W12 units which are linked end‐on to form a macrocyclic assembly containing more iron centers than any other polyoxometalate known to date (see figure).